Validation of case identification for alopecia areata using international classification of diseases coding - Lavian, Jonathan; Li, Sara; Lee, Eunice; Bordone, Lindsey; G. Polubriaginof, Fernanda; Christiano, Angela; Mostaghimi, Arash (International journal of trichology, 2020)
Background: Search algorithms used to identify patients with alopecia areata (AA) need to be validated prior to use in large databases. Objectives: The aim of the study is to assess whether patients with an International Statistical Classification of Diseases and Related Health Problems (ICD) 9 or 10 code for AA have a true diagnosis of AA. Materials and Methods: A multicenter retrospective review was performed at Columbia University Irving Medical Center, Brigham and Women's Hospital, and Massachusetts General Hospital to determine whether patients with an ICD 9 codes (704.01 - AA) or ICD 10 codes (L63.0 -Alopecia Totalis, L63.1 - Alopecia Universalis, L63.2 - Ophiasis, L63.8 - other AA, and L63.9 - AA, unspecified) for AA met diagnostic criteria for the disease. Results: Of 880 charts, 97.5% had physical examination findings consistent with AA, and 90% had an unequivocal diagnosis. AA was diagnosed by a dermatologist in 87% of the charts. The positive predictive value (PPV) of the ICD 9 code 704.01 was 97% (248/255). The PPV for the ICD 10 codes were 64% (75/118) for L63.0, 86% (130/151) for L63.1, 50% (1/2) for L63.2, 91% (81/89) for L63.8, and 93% (247/265) for L63.9. Overall, 89% (782/880) of patients with an ICD code for AA were deemed to have a true diagnosis of AA. Conclusions: Patients whose medical records contain an AA-associated ICD code have a high probability of having the condition.